BioGenTool: A Generic Bio-inspired Neural Tool. - Gan Kim Soon; Chang Sim Vui; Chin Kim On; Patricia Anthony (American Scientific Publishers, 2018)
Artificial neural network (ANN) is a bio-inspired algorithm which has been shown to perform well in many domains in solving non-linear and complex problems. However, in order to apply ANN to solve a particular problem, the implementer is required to not only possess the domain problem knowledge and ANN knowledge but also the programming language knowledge to carry out the experiments. Hence, this paper describes the development of a generic bio-inspired neural tool that provides an interactive and intuitive GUI for setting up ANN experiments for numerical problem domain utilizing feedforward neural network in supervised learning. This tool is developed specifically for researchers with non-computing background who wishes to design an ANN based-solution to a particular numerical problem.